Design criteria for impact factors based on dynamic on-site data in railway bridges. Issue 4 (3rd April 2019) - Jung, Hyunjun; Kim, Gyuseon; Oh, Jintak; Park, Jaebong
Abstract: To evaluate the dynamic behaviours of bridges, many researchers have analysed interactions between vehicles and bridges with numerical methods instead of field loading tests. However, conventional numerical methods take too much time and cost to evaluate the impact factor of bridges in design and maintenance practice. The objective of this study was to propose improved design criteria by using impact factors based on natural frequency rather than span length of railway bridges using dynamic field load-carrying capacity test database. The improved design criteria use a different methodology than that outlined in the International Union of Railway specifications Code. Statistical regressions are applied to more easily estimate the natural frequency of a bridge with a span length of 20 m or longer with steel plate girder or truss superstructures. Calculated impact factors were compared to impact factors obtained from field measurements. Results indicated that the improved method could provide a very reliable estimation for actual impact factors. Since the suggested impact factor criteria are conservative, the proposed method can be used in design and management stages to consider dynamic effects of railway bridges in a more intuitive manner.